(untitled) (Research, Society and Development, 2019)
The aim of this study was to elaborate dry and fresh extracts from M. oleifera leaves, as well as to perform the physicochemical and toxicological characterizations. Initially, the extracts were made by drying and homogenizing techniques of the leaves of M. oleifera, in dry or fresh state. Soon after, the samples were characterized according to the following parameters: water content (Moisture), water activity, ash, lipids, total soluble solids content, total titratable acidity, pH, and vitamin C. The toxicology test was performed. by Artemia salina Leach, which aims to evaluate the toxic effects on biological systems and to predict the possibility of substance toxicity in relation to other systems. The results of the physicochemical analyzes found for the fresh and dry leaves of M. oleifera were, respectively: Water content (Humidity) of 73.38 and 5.49 g / 100 g, AW was 0.89 and 0 , 43 g / 100g, ashes of 2.53 and 8.14 g / 100 g, lipids of 1.27% and 6.87%, the SST was 3.03 and 4.9º Brix, ATT 0.55 and 1.95 g / 100 g, pH 5.7 and 5.68 and vitamin C 1036.323 and 365.26 mg / 100 g. For toxicity against Artemia sp. observed an LD50 of 12,734 mg / kg for M. oleifera in natura leaves and 5,925 mg / kg for dry leaves, where both are considered nontoxic. Given this, it is concluded that the fresh and dried leaves of M. oleifera are an interesting, viable and inexpensive alternative for human food and supplementation, and can be applied in several segments, since they presented physicochemical and toxicological parameters. satisfactory, given the values determined by current legislation, as well as results similar to several studies in the area.